2023
DOI: 10.1177/20406223221148061
|View full text |Cite
|
Sign up to set email alerts
|

State of the art: non-invasive electrical stimulation for the treatment of chronic tinnitus

Abstract: Subjective tinnitus is the perception of sound in the absence of external stimulation. Neuromodulation is a novel method with promising properties for application in tinnitus management. This study sought to review the types of non-invasive electrical stimulation in tinnitus to provide the foothold for further research. PubMed, EMBASE, and Cochrane databases were searched for studies on the modulation of tinnitus by non-invasive electrical stimulation. Among the four forms of non-invasive electrical modulation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 131 publications
0
1
0
Order By: Relevance
“…Taken together, the evidence suggests that TENS may confer transient beneficial effects for tinnitus, but may be due to a high placebo effect and have no obvious long-term benefit. Three recent systematic reviews and meta-analyses likewise concluded that that electrical stimulation may indeed provide a benefit for tinnitus, but high bias is present in most studies and further investigation into the most effective stimulation pattern and modality are needed before recommendation to patients [117][118][119].…”
Section: Transcranial and Transcutaneous Stimulationmentioning
confidence: 99%
“…Taken together, the evidence suggests that TENS may confer transient beneficial effects for tinnitus, but may be due to a high placebo effect and have no obvious long-term benefit. Three recent systematic reviews and meta-analyses likewise concluded that that electrical stimulation may indeed provide a benefit for tinnitus, but high bias is present in most studies and further investigation into the most effective stimulation pattern and modality are needed before recommendation to patients [117][118][119].…”
Section: Transcranial and Transcutaneous Stimulationmentioning
confidence: 99%
“…Using single and repeated sessions of tDCS targeting either the DLPFC or AC have resulted in immediate beneficiary effects in tinnitus patients; however, most of the observed effects were transient and did not translate into long-term improvements [5,10,[24][25][26]29]. Different review papers have evaluated the efficacy of tDCS for the treatment of tinnitus [30][31][32][33][34][35]. Initial studies focused on single or few sessions of tDCS over the prefrontal cortex (PFC) [5,24,36] and auditory cortex [25,26,37,38] or left temporal area (LTA) [39][40][41].…”
Section: Introductionmentioning
confidence: 99%
“…In the meantime, RCTs and controlled trials that linked study quality and n-VNS’s efficacy as a tinnitus treatment with a novel method, at-VNS, were included in a systematic review and meta-analysis, which set them apart entirely from all the RCTs included in both systematic reviews ( Fernández-Hernando et al, 2023 ). Chen et al (2023) introduced a research review that aimed to compile ongoing research from the literature and provide an overview of the many forms of non-invasive electrical stimulation that are currently in use and their usefulness in treating tinnitus without eliminating studies based on the caliber of those studies. De Ridder et al (2021) recently reviewed vagus nerve stimulation for tinnitus, differing completely from our perspective, which only includes taVNS.…”
Section: Introductionmentioning
confidence: 99%